Tau Pathology in Chronic Traumatic Encephalopathy and Alzheimer's Disease: Similarities and Differences - Katsumoto, Atsuko; Takeuchi, Hideyuki; Tanaka, Fumiaki (Frontiers in Neurology, 2019)
Traumatic brain injury (TBI) has been associated with the development of Alzheimer’s disease (AD) because these conditions share common pathological hallmarks: amyloid-β and hyperphosphorylated tau accumulation. However, given recent data it is uncertain if a history of TBI leads to the development of AD. Moreover, chronic traumatic encephalopathy (CTE), caused by repetitive mild TBI and characterized by progressive neurodegeneration with hyperphosphorylated tau, has come to be recognized as distinct from AD. Therefore, it is important to elucidate the clinical outcomes and molecular mechanisms underlying tau pathology following TBI. We summarize the histopathological features and clinical course of TBI in CTE, comparing the tau pathology with that in AD. Following brain injury, diffuse axonal injury and hyperphosphorylated tau aggregates are observed within a shorter period than in AD. Hyperphosphorylated tau deposition usually begins in the perivascular area of the sulci in the cerebral cortex, then spreads unevenly in the cortex in CTE, while AD shows diffuse distribution of hyperphosphorylated tau in the cortical areas. We also highlight the molecular profile of tau and the implications of tau progression throughout the brain in both diseases. Tau contains phosphorylation sites common to both conditions. In particular, phosphorylation at Thr231 triggers a conformational change to the toxic cis form of tau, which is suggested to drive neurodegeneration. Although the mechanism of rapid tau accumulation remains unknown, the structural diversity of tau might result in these different outcomes. Finally, future perspectives on CTE in terms of tau reduction are discussed.